A Retrospective evaluation of hysterolaparoscopy as primary diagnostic tool for female infertility - Jamal, Shehla; Sharma, Mridula; Masroor, Kainat; Singh, Shravi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Infertility has been equally challenging and frustrating to the couple as well as physician. The causative etiology can have multitude of factors. Evaluation of underlying factors and formulating uniform diagnostic protocols is still a challenge for most of the infertility experts. This study was aimed to evaluate hysterolaparoscopy as primary diagnostic tool for female infertility. Methods: This is a retrospective study conducted in the department of obstetrics and gynecology, SMS and R, Sharda University, Greater Noida, Uttar Pradesh. The data was collected from January2018 to December 2019. A total of 84 cases were studied. Data were entered into Epi-data version 3.1 and then exported to SPSS version 20 for cleaning and analysis. Chi-square test and logistic regression were done. Results: Around 86.9% of the patients had abnormal findings. 13% of the patients had no abnormal laparoscopic findings, according to our inclusion criteria. One or the other findings were encountered in 96.4% of the cases. Only 3.5% of the patients had no discernible characteristics as per our inclusion protocol. Conclusions: Irrespective of the investigations protocols used, hysterolaparoscopy finds its importance in most of the clinical settings. This investigative approach is professed as superior to hysterosalpingogram and Saline Infusion sonography when used alone. In the present study, we propose diagnostic hysterolaproscopy as first and one step approach, between days 8-11 of the cycle, as an effective diagnostic tool in cases of infertility.